2002
DOI: 10.1038/sj.jhh.1001447
|View full text |Cite
|
Sign up to set email alerts
|

Effects of efonidipine on platelet and monocyte activation markers in hypertensive patients with and without type 2 diabetes mellitus

Abstract: We compared the levels of microparticles, platelet activation markers, soluble cell adhesion molecules, and soluble selectins between hypertensive patients with and without type 2 diabetes and control subjects. Binding of anti-glycoprotein IIb/IIIa and anti-glycoprotein Ib monoclonal antibodies to platelets did not differ significantly between the hypertensive patients and controls, but platelet expression of activation markers (CD62P, CD63, PAC-1, and annexin V) was higher in the hypertensive patients. Platel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
65
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 57 publications
4
65
1
2
Order By: Relevance
“…11 We previously reported that a high level of monocyte-derived microparticles (MDMP) may be a marker of vasculopathy in diabetic patients. [12][13][14][15][16] Adiponectin is the most abundant fat-specific hormone, being exclusively expressed by and secreted from adipose tissue. 17 The plasma adiponectin concentration is decreased in obese individuals 17,18 and patients with type 2 diabetes, 19 and its level is closely related to whole-body insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…11 We previously reported that a high level of monocyte-derived microparticles (MDMP) may be a marker of vasculopathy in diabetic patients. [12][13][14][15][16] Adiponectin is the most abundant fat-specific hormone, being exclusively expressed by and secreted from adipose tissue. 17 The plasma adiponectin concentration is decreased in obese individuals 17,18 and patients with type 2 diabetes, 19 and its level is closely related to whole-body insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, the four studies [3][4][5][6] have verified a role of increased platelet and endothelial activity, monocytes, cell adhesion molecules and microparticles in the pathogenesis of hypertension (alone or concurrent with diabetes). Therefore, antihypertensive medication that has simultaneous antiatherogenic or favourable haemorheological effects is likely to be significant in the prevention of vascular morbidity and mortality.…”
mentioning
confidence: 89%
“…In addition, similar to hypertensives, platelets, selectins and indicators of cell adhesion may be of pathogenic importance in the microvascular and macrovascular complications of diabetes. Nomura et al 6 compared the levels of cell adhesion molecules and markers of both monocyte and platelet activation in 48 middle-aged hypertensive patients (23 of whom had type 2 diabetes) and 30 controls. In addition, the impact of 8-week treatment with efonidipine, a calcium channel blocker, on the levels of these factors was assessed.…”
mentioning
confidence: 99%
“…22,36 As Rizzoni and colleagues report, many risk factors for atherosclerosis, including diabetes and hypertension, are generally (though not always) associated with increased levels of sICAM-1 and sVCAM-1. 26,[37][38][39][40][41][42][43] It is unclear whether the observed elevations are because of direct effects or to subclinical atherosclerosis. Certainly, elevated levels of both sICAM-1 and sVCAM-1 have been documented in patients with essential hypertension without overt atherosclerotic disease, 39 although in this cohort of elderly (mean age 69 years) hypertensive men it seems likely that some would have inapparent disease.…”
Section: Soluble Icam-1 and Vcam-1 As Markers Of Atherosclerosismentioning
confidence: 99%